Multi-fire-proxy record of sediment core GeoB10053-7 - Ruan, Yanming (PANGAEA, 2020)
This file contains three spreadsheets. The spreadsheet 'Levoglucosan' contains the concentration and accumulation rate of the compound levoglucosan. The spreadsheet 'PAHs' contains the concentration and accumulaition rate of individual PAHs compounds and their sum. The ratio of IP/(IP+BghiP) and the normalised ratio of (LVG/LVG+PAHs) are also included. The spreadsheet 'Micro-charcoal' contains the micro-charcoal particle count and its accumulation rate.
Keywords: levoglucosan; micro-charcoal; PAH